Suffering without Suffrage: Why Felon Disenfranchisement Constitutes Vote Denial under Section Two of the Voting Rights Act - Feinberg, Matthew E. (2011)
This article explores state felon disenfranchisement laws and proposes a new way for felons to challenge the legality of excluding them from the democratic process. Despite the seemingly explicit grant of authority in the Fourteenth Amendment to exclude felons from the voting process, this article posits that the Voting Rights Act provides an alternative, and more attractive, vehicle for felons to secure the right to vote. This article examines the current Circuit split on whether the Voting Rights Act even allows for or contains a cause of action to challenge felon disenfranchisement laws. Concluding that it does, the article moves forward to suggest a test that the Supreme Court should adopt to determine whether state disenfranchisement laws violate the Voting Rights Act